Role of labour admission test in predicting pregnancy outcome in low-risk cases - Syeda, Bushra B.; Kulakarni, Sunanda R.; Chinna, Althaf H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The present study was carried out to determine the role of labour admission test (LAT) in detecting fetal hypoxia in labour and to correlate the findings of the test with perinatal outcome in low-risk cases. Methods: In this study 150 low risk pregnant term women were subjected to LAT and classified according to NICE 2017 guidelines. Pregnancy outcome in terms of need for operative delivery and neonatal status at birth were noted. Data was analysed statistically by Chi-square test. Results: The LAT was normal in 78.67%, suspicious in 17.33% and pathological in 4%. Operative delivery for fetal distress was observed in 18.75% of normal group, in 50% of suspicious group and in 100% of pathological group. The incidence of meconium-stained liquor was significantly high in pathological (50%) and suspicious group (19.23%). The incidence of low 5-minute Apgar score was significantly high in pathological LAT group (33.33%) as compared to suspicious (7.69%) and normal LAT groups (2.54%). Admission to neonatal intensive care unit (NICU) was significantly high in pathological test group (50%). LAT in this study showed 48.15% sensitivity, 96.75% specificity and 76.47% positive predictive value as a screening tool for predicting fetal distress in low-risk patients suggesting that a normal LAT in early labour is an indicator of good pregnancy outcome. Conclusions: LAT is an effective, non-invasive screening method with good specificity to detect fetal distress in low-risk woman and helps to plan management accordingly to improve pregnancy outcome.